2014
DOI: 10.1080/10548408.2014.873318
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Social Media on Chinese Students’ Choice of an Overseas Study Destination: An Information Adoption Model Perspective

Abstract: This study is an experimental investigation of the influence of social media on choosing an overseas study destination. The elaboration likelihood model of communication and persuasion provides a conceptual basis for this study. Data was collected through convenience sampling of Chinese students from three Brisbane tertiary institutions. Participants were provided with one of the four treatments with manipulated stimuli. Results suggest that social media content is an influential factor in determining destinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
66
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(99 citation statements)
references
References 45 publications
8
66
0
4
Order By: Relevance
“…Argument quality refers to the quality of content/message contained in the travel destination-related eWOM. Source credibility and argument quality of social media material are empirically tested to be related with attitude formation in the context such as outbound studying destination choice [25] and adoption of accommodation related online review [4]. Thus, we propose that argument quality and source credibility of destination-related eWOM have positive influence on tourists' attitude towards the destination.…”
Section: Fig 1 Elaboration Likelihood Modelmentioning
confidence: 99%
“…Argument quality refers to the quality of content/message contained in the travel destination-related eWOM. Source credibility and argument quality of social media material are empirically tested to be related with attitude formation in the context such as outbound studying destination choice [25] and adoption of accommodation related online review [4]. Thus, we propose that argument quality and source credibility of destination-related eWOM have positive influence on tourists' attitude towards the destination.…”
Section: Fig 1 Elaboration Likelihood Modelmentioning
confidence: 99%
“…Previous research in tourism points out user-generated content can be regarded as the main factor which influences tourists' travel decision-making (Ayeh, Au & Law, 2013;Bizirgianni, & Dionysopoulou, 2013;Fotis, 2012;Jacobsen & Munar, 2012;Shu & Scott, 2014;Xiang & Gretzel, 2010), purchasing behavior (Boley, Magnini & Tuten, 2013;Huang, Chou & Lin, 2010;Sparks, Perkins & Buckley, 2013;Ye et al, 2011) and trip evaluation (Bronner & Hoog, 2011). On the other hand, user-generated content can be utilized as a new vehicle for enterprises to understand consumers' attitudes towards tourism products (Dellarocas, Zhang & Awad, 2007) and provide potential for tourism organizations to research and update market status (Akehurst, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…China Internet Network Information Center (CNNIC) (2014) reported that Chinese internet users had reached 618 million by the end of 2013, and the nationwide penetration rate of the Internet was 45.8 percent, increased by 3.7 percent from 2012. Chinese Internet users spent 2.7 hours a day on the Internet which is even higher than some developing countries, while restrictions on some foreign social media such as Facebook and YouTube in Mainland China has propelled the rapid development of Chinese indigenous social media (Shu & Scott, 2014). The high popularity of all these homegrown social media platforms assists an increasing number of government agencies and tourism organizations to promote city or destination images (Zhou & Wang, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Los mochileros chinos, también llamados Donkey Friends, son un grupo de turistas jóvenes que tienen diferentes preferencias de viaje (Ong y Du Cros, 2012;Chen et al, 2013), aunque su denominador común es el interés por la libertad de espíritu y la autorrealización (Chen y Weiler, 2014). Otro campo de estudio que ha despertado el interés es el comportamiento turístico de los jóvenes chinos que estudian fuera de su país (Shu y Scott, 2014) y protagonizan un modelo de turismo diferente que los estudiantes de otras nacionalidades, ya que en sus viajes están más interesados en la cultura y el patrimonio que en la diversión y el ocio (Xu et al, 2009;King y Gardiner, 2015). Además, estos estudiantes tienen un importante papel atrayendo más turistas y esparciendo comentarios positivos sobre el destino (Liu y Ryan, 2011;Chen et al, 2015) .…”
Section: B) Estudios De Segmentos Minoritarios Concretosunclassified